2021
DOI: 10.1155/2021/5515218
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Common and Cancer-Specific Differently Expressed lncRNAs in Urologic Cancers

Abstract: Urologic cancers, comprising prostate carcinoma (PCa), renal cell carcinoma (RCC), and bladder carcinoma (BCa), were the commonly occurred carcinoma amid males. Long noncoding RNAs (lncRNAs) with the length of more than 200 nt functioned importantly in physiological and pathological advancement. Nevertheless, further investigation regarding lncRNA expression feature and function in urologic cancers should be essential. This study is aimed at uncovering the roles of the differently expressed lncRNAs in urologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Through GO analysis, the authors found that pRCC-specific lncRNAs were primarily involved in the morphogenesis of cilium, the process of metabolic, oxidation of fatty acid beta, homeostasis of lipid, and fatty acid beta-oxidation, using acyl-CoA dehydrogenase. KEGG analysis suggested that pRCC-specific lncRNAs principally took part in metabolic pathways, staphylococcus aureus infection, biosynthesis of antibiotics, valine, leucine, and isoleucine degradation, and carbon metabolism [159]. The dysregulation of DLGAP1-AS3, SPON1, ULK4P3, RPL34-AS1, RP11-557H15.3, RP11-368J21.3, ANKRD18DP, LINC00607, and ADORA2A-AS1 were significantly correlated to OS in pRCC and could thus serve as prognostic markers [159].…”
Section: Prognostic Long Non-coding Rna In Tcga Datasetmentioning
confidence: 99%
See 4 more Smart Citations
“…Through GO analysis, the authors found that pRCC-specific lncRNAs were primarily involved in the morphogenesis of cilium, the process of metabolic, oxidation of fatty acid beta, homeostasis of lipid, and fatty acid beta-oxidation, using acyl-CoA dehydrogenase. KEGG analysis suggested that pRCC-specific lncRNAs principally took part in metabolic pathways, staphylococcus aureus infection, biosynthesis of antibiotics, valine, leucine, and isoleucine degradation, and carbon metabolism [159]. The dysregulation of DLGAP1-AS3, SPON1, ULK4P3, RPL34-AS1, RP11-557H15.3, RP11-368J21.3, ANKRD18DP, LINC00607, and ADORA2A-AS1 were significantly correlated to OS in pRCC and could thus serve as prognostic markers [159].…”
Section: Prognostic Long Non-coding Rna In Tcga Datasetmentioning
confidence: 99%
“…KEGG analysis suggested that pRCC-specific lncRNAs principally took part in metabolic pathways, staphylococcus aureus infection, biosynthesis of antibiotics, valine, leucine, and isoleucine degradation, and carbon metabolism [159]. The dysregulation of DLGAP1-AS3, SPON1, ULK4P3, RPL34-AS1, RP11-557H15.3, RP11-368J21.3, ANKRD18DP, LINC00607, and ADORA2A-AS1 were significantly correlated to OS in pRCC and could thus serve as prognostic markers [159].…”
Section: Prognostic Long Non-coding Rna In Tcga Datasetmentioning
confidence: 99%
See 3 more Smart Citations